Oxidation of bisphenol A from simulated and real urban wastewater effluents by UV, O3 and UV/O3. Issue 3 (14th January 2016) - Dudziak, Mariusz; Burdzik, Edyta
Abstract: Increased concentration of micropollutants in the aquatic environment triggers the necessity to develop more effective methods for their elimination. A variety of research has been devoted to similar subject matters regarding the efficiency of different advanced oxidation processes to eliminate micropollutants. On the basis of them, this study was undertaken so as to assess the efficiency of bisphenol A (BPA) elimination from both stimulated and real urban wastewater effluents by photolysis (UV), ozonation (O3 ) and UV/O3 processes. The obtained results were juxtaposed in terms of the efficiency of BPA elimination for deionised water. The physical and chemical composition of the solution differentiated BPA elimination efficiency in the investigated processes. BPA decomposition degree was higher for real wastewater effluents than for deionised water and stimulated effluents. It is probably connected with the presence of photosensitisers in the real effluent. It was established that the combination of photolysis and ozonation led to the highest level of compound decomposition (for real effluent >90%). In this research, a first-order reaction model was used to establish the reaction rate constant for BPA decomposition in a combined UV/O3 process. The half-life of the investigated compound was also identified.